A new assessment tool for patients with multiple sclerosis from Spanish-speaking countries: validation of the Brief International Cognitive Assessment for MS (BICAMS) in Argentina. Issue 7 (2nd October 2016) - Vanotti, Sandra; Smerbeck, Audrey; Benedict, Ralph H. B.; Caceres, Fernando
Abstract: Background: The Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) is an international assessment tool for monitoring cognitive function in multiple sclerosis (MS) patients. BICAMS comprises the Symbol Digit Modalities Test (SDMT), the California Verbal Learning Test – Second Edition (CVLT II) and the Brief Visuospatial Memory Test – Revised (BVMT-R). Our objective was to validate and assess the reliability of BICAMS as applied in Argentina and to obtain normative data in Spanish for this population.Method: The sample composed of 50 MS patients and 100 healthy controls (HC). In order to test its reliability, BICAMS was re-administered in a subset of 25 patients.Results: The sample's average age was 43.42 ± 10.17 years old, and average years of schooling were 14.86 ± 2.78. About 74% of the participants were women. The groups did not differ in age, years of schooling, or gender. The MS group performed significantly worse than the HC group across the three neuropsychological tests, yielding the following Cohen's d values: SDMT: .85; CVLT I: .87; and BVMT-R: .40. The mean raw scores for Argentina normative data were as follows: SDMT: 56.71 ± 10.85; CVLT I: 60.88 ± 10.46; and BVMT-R: 23.44 ± 5.84. Finally, test–retest reliability coefficients for each test were as follows: SDMT: r  = .95; CVLT I: r  = .87; and BVMT-R: r  = .82.Conclusion: This BICAMS version is reliable and useful as a monitoring tool for identifying MS patients with cognitive impairment.